2016
DOI: 10.3389/fpls.2016.01296
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-Mediated Abiotic Stress Signaling in Roots

Abstract: Roots are subjected to a range of abiotic stresses as they forage for water and nutrients. Cytosolic free calcium is a common second messenger in the signaling of abiotic stress. In addition, roots take up calcium both as a nutrient and to stimulate exocytosis in growth. For calcium to fulfill its multiple roles must require strict spatio-temporal regulation of its uptake and efflux across the plasma membrane, its buffering in the cytosol and its sequestration or release from internal stores. This prompts the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
87
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(101 citation statements)
references
References 217 publications
(348 reference statements)
8
87
1
2
Order By: Relevance
“…Thus, in the present study, lncRNAs targeting the eight upregulated GOLS genes may participate in RFO synthesis in response to salt stress. The Ca 2+ signaling pathway was also reported to mediate plant response to salt stress, which starts with Ca 2+ transporters such as Ca 2+ -ATPases, Ca 2+ sensors, and relay proteins such as CaM, CMLs, CDPKs, CBLs, and CIPKs (Wilkins et al, 2016). LncRNAs targeting calcium-transporting ATPase, calmodulin-interacting protein, CDPKs and CIPKs in this study were predicted to be involved in salt-stress response through the Ca 2+ signaling pathway.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Thus, in the present study, lncRNAs targeting the eight upregulated GOLS genes may participate in RFO synthesis in response to salt stress. The Ca 2+ signaling pathway was also reported to mediate plant response to salt stress, which starts with Ca 2+ transporters such as Ca 2+ -ATPases, Ca 2+ sensors, and relay proteins such as CaM, CMLs, CDPKs, CBLs, and CIPKs (Wilkins et al, 2016). LncRNAs targeting calcium-transporting ATPase, calmodulin-interacting protein, CDPKs and CIPKs in this study were predicted to be involved in salt-stress response through the Ca 2+ signaling pathway.…”
Section: Discussionmentioning
confidence: 61%
“…Notably, 42 cis-and 67 trans-target genes were differentially expressed under salt stress. Among these target genes, Ca 2+ -transporting ATPase (TEA027212.1) was reported to be an important gene in Ca 2+ signaling under abiotic stress (Wilkins et al, 2016), which suggests that its corresponding lncRNA, MSTRG.139242.1, may interact with Ca 2+ -transporting ATPase and may be involved in this process. Thus, a gene suppression assay of MSTRG.139242.1 and TEA027212.1 (Ca 2+ -transporting ATPase 13) using AsODNs was conducted and suggested that lncRNA MSTRG.139242.1 may be regulated by its nearby coding gene, TEA027212.1.…”
Section: Discussionmentioning
confidence: 99%
“…The rise in the cytosolic Ca 2C in response to Cd 2C has been shown to be due to transportation of external Ca 2C through the Cch1p/Mid1p channel. 42 Based on the dose and the ability for the generation of hydroxyl radicals, the heavy metals regulate calcium in roots.…”
Section: B=w In Print; Colour Onlinementioning
confidence: 99%
“…Ca 2+ , an important secondary messenger, plays a key role in the plant response to biotic or abiotic stress (Ranty et al, 2016;Wilkins, Matthus, Swarbreck, & Davies, 2016). Extracellular Ca 2+ decreases the K + loss induced by NaCl in Arabidopsis root epidermal protoplasts by blocking K + efflux channels (Shabala et al, 2006); however, it is unknown whether herbivore regulates the Ca 2+ signal during the plant response to NaCl stress.…”
Section: He Enhances Cytosolic Ca 2+ Accumulation By Increasing Ca mentioning
confidence: 99%
“…Plants have evolved complex strategies to avoid or resist the effects of environmental stresses. Ca 2+ , a ubiquitous secondary messenger and early signalling component, plays essential roles in the plant's defence against both abiotic and biotic stresses (Ranty et al, 2016;Wilkins et al, 2016). The success of the plant's defence response therefore depends on the rapid recognition of stress and the translation of this information into Ca 2+ signals (Santamaria, Arnaiz, Gonzalez-Melendi, Martinez, & Diaz, 2018;Shabala, Wu, & Bose, 2015).…”
Section: The Signalling Molecule Ca 2+ Functions In Plant Response mentioning
confidence: 99%